2021
DOI: 10.3390/nu13103491
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Relationship between Vitamin D and Insulin Resistance: Impact on Clinical Practice

Abstract: Recent evidence has revealed anti-inflammatory properties of vitamin D as well as extra-skeletal activity. In this context, vitamin D seems to be involved in infections, autoimmune diseases, cardiometabolic diseases, and cancer development. In recent years, the relationship between vitamin D and insulin resistance has been a topic of growing interest. Low 25-hydroxyvitamin D (25(OH)D) levels appear to be associated with most of the insulin resistance disorders described to date. In fact, vitamin D deficiency m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 191 publications
(236 reference statements)
1
38
0
1
Order By: Relevance
“…The results suggest that VD supplementation may help increase insulin sensitivity and glycemic control in T2DM patients participating in a training intervention ( 28 ). It has been demonstrated in in vivo and in vitro studies that VD plays an important role in maintaining pancreatic ß-cell function, among others, by regulating calcium flux ( 39 ). Experimental studies have also shown that VD may help reduce the accumulation of advanced glycation end-products which have been linked to insulin resistance ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that VD supplementation may help increase insulin sensitivity and glycemic control in T2DM patients participating in a training intervention ( 28 ). It has been demonstrated in in vivo and in vitro studies that VD plays an important role in maintaining pancreatic ß-cell function, among others, by regulating calcium flux ( 39 ). Experimental studies have also shown that VD may help reduce the accumulation of advanced glycation end-products which have been linked to insulin resistance ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in in vivo and in vitro studies that VD plays an important role in maintaining pancreatic ß-cell function, among others, by regulating calcium flux ( 39 ). Experimental studies have also shown that VD may help reduce the accumulation of advanced glycation end-products which have been linked to insulin resistance ( 39 ). Therefore, VD intake may have additional beneficial effects on insulin secretion and skeletal muscle insulin sensitivity, particularly in VD-deficient patients, compared with training only.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of muscle mass in older people is also related to low serum levels of vitamin D [ 15 , 16 ]. Notably, in obesity, low vitamin D is consistently found across age, ethnicity, and geography [ 17 ], and vitamin D has been thoroughly investigated in relation to insulin resistance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vit D is activated in the body to acquire the biological activity of a hormone, with 1, 25-bishydroxyvitamin D3 acting as its main active form. According to related studies, Vit D level may be a protective factor against the development of IR ( 12 15 ). However, this conclusion is considered controversial at present.…”
Section: Introductionmentioning
confidence: 99%